2013
DOI: 10.1080/00219266.2013.837402
|View full text |Cite
|
Sign up to set email alerts
|

Students’ understanding of genetics concepts: the effect of reasoning ability and learning approaches

Abstract: Students tend to learn genetics by rote and may not realise the interrelationships in daily life. Because reasoning abilities are necessary to construct relationships between concepts and rote learning impedes the students' sound understanding, it was predicted that having high level of formal reasoning and adopting meaningful learning orientation would improve students' understanding of genetics concepts. To test this hypothesis, relationships among students' understanding of genetics concepts, reasoning abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
1
35
0
2
Order By: Relevance
“…This means that as students' rote learning orientation scores increased, their learning levels decreased and possessed more misconceptions. Likewise, Kılıç and Sağlam (2014) investigated the effects of logical thinking ability, and meaningful and rote learning orientation on 11 th grade students' understanding levels of concepts of genetics, and concluded that logical thinking ability and meaningful learning orientation had a statistically significant and effect in a positive direction whereas rote learning orientation had a significant effect in negative direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that as students' rote learning orientation scores increased, their learning levels decreased and possessed more misconceptions. Likewise, Kılıç and Sağlam (2014) investigated the effects of logical thinking ability, and meaningful and rote learning orientation on 11 th grade students' understanding levels of concepts of genetics, and concluded that logical thinking ability and meaningful learning orientation had a statistically significant and effect in a positive direction whereas rote learning orientation had a significant effect in negative direction.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of developing students' reasoning abilities, logical relationships which they will establish between evidences and misconceptions will enable students to have fewer misconceptions. Some studies stated that students' orientations towards learning and reasoning abilities were also effective on their levels of understanding topics of genetics (Cavallo, 1996;Kılıç & Sağlam, 2014). Although some studies conducted on elementary school (Baser & Geban, 2007) determined that students' reasoning abilities had a positive effect on their understandings of concepts of heat and temperature, there are no studies conducted to determine what kind of an effect they have on high school students' understandings of HTIE concepts.…”
Section: Introducationmentioning
confidence: 99%
“…Genetics is one of the pure biological sciences included on the biotechnology field. The vast majority of a society is only informed about genetics development through mass media and this may lead to lack of information (Kılıç and Sağlam 2014). Hott et al (2002) emphasised that, given the increasing importance of genetics in daily life, it is important that the education system should increase public understanding of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the processing results, we calculated the comprehensive evaluation model shown in the formula: (17) where F 2 is the comprehensive score; and Z i indicates the standard value of achievement indicator i.…”
Section: (2) Achievement Index Evaluationmentioning
confidence: 99%
“…The Douglas's cost function with stochastic frontier characteristics can be defined as [15][16][17]:…”
Section: Operational Efficiency Evaluation Model Based On Stochasticmentioning
confidence: 99%